Exploring the Mother–Adolescent Relationship as a Promotive Resource for Sexual and Gender Minority Youth. (21st September 2017) - Bouris, Alida; Hill, Brandon J.
Abstract: Research often analyzes gender minority youth and sexual minority youth as a single group, a practice that obscures differences in how gender identity and sexual orientation shape health. The present study uses intersectionality to explore similarities and differences in the relationships between minority stress theory variables in a sample of 28 gender minority and 135 sexual minority youth of color. We also explore the mother–adolescent relationship as a potential promotive resource for minority stress research with youth. Results find few differences in minority stressors, promotive resources, or health between sexual and gender minority youth. However, different patterns in the correlations between stressors, resources, and health were observed for each group, underscoring the need for researchers to consider sexual and gender minority youth as distinct groups. Furthermore, study findings suggest that the maternal relationship may be an important promotive resource for both sexual and gender minority youth.